The Influence Of Employee Engagement And Job Satisfaction On Employee Performance At Regional Development Planning Agency, Seluma Regency - Eka Vitri Yulita; Ahmad Soleh; M. Rahman Febliansa (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the effect of employee engagement and job satisfaction on employee performance at the Regional Development Planning Agency of Seluma Regency. The sample in this study were 122 ASN and honorary employees at the Regional Development Planning Agency of Seluma Regency. Data collection techniques using a questionnaire. The analytical method used is multiple regression analysis, hypothesis testing t and hypothesis testing f.The results of the regression equation, namely the results of the regression equation, namely Y = 8.228 + 0.487X1 + 0.312X2 means that employee engagement and job satisfaction have a positive influence on employee performance at the Regional Development Planning Agency of Seluma Regency. This illustrates that if the employee engagement and job satisfaction variables increase, employee performance will also increase. The result of the determination test is 0.457 or (45.7%). This shows that employee engagement and job satisfaction affect employee performance by 45.7%, while the rest (100 - 45.7% = 54.3%) is explained or influenced by other variables not examined. Employee engagement and job satisfaction jointly have an influence on employee performance at the Regional Development Planning Board of Seluma Regency with a value of Fcount > Ftable (50.020 > 3.07) in line with a significance of 0.000 <0.05. Employee engagement has a positive and significant effect on employee performance at the Regional Development Planning Agency of Seluma Regency, because the tcount is greater than ttable (4.195 > 1.657) with a significance value of 0.000, less than 0.05. Job satisfaction has a positive and significant effect on employee performance at the Regional Development Planning Agency of Seluma Regency, with a tcount greater than ttable (2.970 > 1.657) with a significance value of 0.004, less than 0.05.